A facile green and cost-effective manufacturing process from coal gangue-reinforced composites. (1st March 2023) - Li, Chao; Liao, Hongqiang; Gao, Hongyu; Zhang, Huirong; Cheng, Fangqin
Abstract: Utilization of high-filler coal gangue (CG) to produce cost-effective composites is a promising strategy. To clarify the impact of high-filled CG on composite preparation and performance, in this research, the composite was prepared from CG and polyethylene (PE) through physical mixing and then hot-pressing. The role of CG in the properties of the composites and the influence of the interface formation mechanism are obtained by establishing the relationship between CG content and the composites' feature. The results show that: high-filler CG is helpful to the increment of the composite's mechanical and thermostable properties. When the CG addition is up to 80%, the density and hardness from 0.93 g/cm 3 and 50.5 HD increased to 1.60 g/cm 3 and 66.5HD, which was increased by 72.0% and 31.6%, respectively. Meanwhile, the bending strength and modulus reach 17.5 MPa and 3400.6 MPa, which is respectively exceeded by 56.3% and 628.6% than composite from pure PE (11.2 MP and 466.7 MPa). In addition, high-filler CG is beneficial for the enhancement of entanglement between CG and PE during the composite preparation, and has the effect of heterogeneous nucleation, which facilitated the crystallization and thermal stability of the composite. The properties of the composites prepared by this simple technique meet national standards and are more economical and environmentally sustainable than composites prepared with other fillers. This new material holds great promise for the development and realisation of carbon-neutral decorative materials such as assembly buildings, vehicles and coloured panels. Graphical abstract: Image 1 Highlights: A novel process for the high utilization of coal gangue was proposed in the polymer. A low-cost and green composite was prepared with coal gangue and polyethylene. The mechanism of CG-based composite formation was revealed. The economic and environmental effects of composites were evaluated.